Changes to the state aid rules in response to the crisis due to the spread of Covid-19 - Simeonova, Ginka (Law Journal of New Bulgarian University, 2021)
In these extraordinary times for the world’s economies, it is inevitable that Member States will support their economies in entire sectors and industries, including through public resources. However, this approach must be followed carefully, as such allocation of public resources in the form of state support is subject to strict state aid rules. The article examines the changes in the state aid regime that the economic consequences of the spread of COVID- 19 have imposed.